Clinical and functional evaluation of bone marrow aspirate concentrate vs autologous conditioned serum in the treatment of knee osteoarthritis - Vitali, Matteo; Ometti, Marco; Pironti, Pierluigi; Salvato, Damiano; Sandrucci, Alice; Leone , Orlando; Salini, Vincenzo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The aim of this study was to compare the efficacy of a single Bone Marrow Aspirate Concentrate (BMAC) with a cycle of 4 Autologous Conditioned Serum (ACS) injections in the treatment of early-stage knee osteoarthritis (OA).Methods: Two groups of 12 patients with degenerative knee OA were treated with a single BMAC injection and with a cycle of 4 ACS injections respectively. Follow-up was set at baseline (t0), one-month (t1) and six-months (t2) evaluating VAS for pain, WOMAC index and range of motion (ROM).Results: We reported a significant improvement in WOMAC after BMAC injection both at t1 (p= 0,001) as well as t2 (p< 0,001), plus a reduction of VAS values in BMAC group at six months follow-up (p = 0,024). In contrast, no significant differences in ROM between the two groups were observed.Conclusions: Both the approaches are safe and effective in the treatment of knee OA, with a major efficacy of BMAC.